Modeling for the Stringency of Lock-Down Policies: Effects of Macroeconomic and Healthcare Variables in Response to the COVID-19 Pandemic - Santini, Giunio; Fordellone, Mario; Boffo, Silvia; Signoriello, Simona; De Vito, Danila; Chiodini, Paolo (Frontiers in Public Health, 2022)
Background. The spread of Covid-19 pandemics has been characterized by unprecedented global lock-downs. Although, the extent of containment policies cannot be explained only through epidemic data. Previous studies already focused on the relation between the economy and healthcare, focusing on the impact of diseases in countries with a precarious economic situation. However, the pandemic event caused by SARS-CoV-2 drew most countries of the world into a similar phenomenon. Methods. A discriminant analysis performed via partial least squares procedure was applied to evaluate the impact of economic and healthcare variables on the containment measures adopted by 39 countries. To collect the input variables (Macroeconomic, Healthcare Services, Medical), we relied on official databases of international organizations, such as The World Bank and World Health Organization. Results. Our findings indicate that the stringency of containment measures could not only be explained through the differences in the impact of the Covid-19 pandemic but also by the economic and healthcare conditions characterizing a country could be as relevant as the epidemiological indexes in shaping the extent of lock-down measures. Conclusions. Indeed, economic and healthcare variables also contributed to shaping the implemented lock-down policies.